STUDY OF FLARE PROBABILITY BY EXAMINING SUNSPOTS' FEATURE AND ENVIRONMENT. - Lailatus Syarifah, Zuhoi
Solar activity produces several major events that affect the surrounding environment including Earth, one of which is a flare event. Most of the flares occur in active areas where there are many sunspots which tend to appear in groups. Sunspot groups in general have evolved both in terms of magnetic configuration, sunspot area, and the environment around the main sunspot. Flares may have a direct impact on Earth within only minutes after the flare occurs. The effect of these flares could be informs of damages to Earth and space-based technologies, such as satellites and radio. The great impact of these flares has made scientists conduct research to predict the occurrence of flares as an effort to prepare strategic steps to reduce the impact of flares on Earth. This research was conducted to study the correlation between sunspot features and their environment with the possibility of flares occurring and the effects of flares on the sunspot environment. The study was conducted by utilizing HMI Continuum imagery data from the SDO satellite and data compiled on solarmonitor.org. The sunspot data that is the focus of this research consist of at least two sunspots for each class of flares and those that do not produce flares around the solar equator. This research is expected to provide insight into the pattern of environmental evolution of sunspots and their relation to the probability of flares. Environmental analysis of sunspots with the probability of flares is carried out by taking into account sunspot features which include changes in sunspot morphology, number of spots, and the size of the sunspot area. The results showed that a measurable evolution of sunspot features was seen in the form of an increase in activity by looking at the appearance of the sunspot along with a flare event. Likewise, after a flare event, the features that are the object of research show decreased activity. However, in contrast to sunspots which do not produce flares, the pattern of environmental evolution tends to decreasing activity as the sunspot ages.